Bridging Healthcare and Community: A Systematic Review of the Role and Impact of Medical Social Workers in Patient-Centered Care - Abusaq, Saddam Hussain; algshaneen, Saad Mohmmad; Al Sedran, Mohammed Shaeil; Obyan , Naif Masood; Alyami, Hamad Mahdi Salem; Zubayd , Fahad Hussain Saleh; Qureshah , Ali Mohammed Hamad; Alsalem, Ibraheem Mohammed; Alyami, Ali Hamad Al rakah; Al garad, Mansour Mohammed Mansour (Journal of Ecohumanism, 2024)
Medical social workers play a pivotal role in bridging the gap between healthcare systems and communities, addressing the social determinants of health, and promoting patient-centered care. This systematic review explores the scope, contributions, and impact of medical social workers in enhancing healthcare delivery and patient outcomes. A comprehensive search of peer-reviewed literature from 2016 onward identified key areas where medical social workers improve care, including patient advocacy, psychosocial support, care coordination, and reducing health disparities. Findings highlight their role in improving patient satisfaction, reducing hospital readmissions, and enhancing quality of life. However, challenges such as limited resources and systemic healthcare barriers remain significant. This review underscores the importance of integrating medical social workers into multidisciplinary healthcare teams to improve holistic care and suggests policy and research directions to strengthen their contributions.